Digital Indonesian Arabic Dictionary For Improving Mastery Of Arabic Vocabulary - Taufiqurrochman, R.; Shirotol Mustaqim, Nur Yasin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Mastery of Arabic vocabulary is very important for Indonesian Umrah pilgrims. In today's digital era, the difficulties in mastering vocabulary faced by pilgrims can be overcome by developing digital dictionaries. This study aims to develop and evaluate an Android-based Digital Indonesian Arabic Dictionary and Website. This study used the ADDIE Model. The instruments used were user assessment questionnaires, vocabulary mastery tests, interviews, and participatory observations. Data analysis using Paired Sample T-Test. From the comparison of pre-test and post-test scores of users of the Digital Indonesian Arabic Dictionary, it is known that there is an increase in mastery of Arabic vocabulary in Indonesian Umrah Hajj pilgrims. They rated this dictionary product as good, sufficient, and excellent in aspects: user interface, word search, usage examples, translation features, and application quality. The Digital Indonesian Arabic Dictionary still has to be developed with new technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), Big Data, Metaverse, and so on.